Megaformalism of living. Genealogy and prerogatives of a potential morpho-technotype - Oscar Eugenio Bellini; Marianna Arcieri (Agathón)
The research for new forms of shared housing, able to face the multiple environmental and social criticalities of the planet, is driving to rethink the conventional ways of living together. In this context, the Megaform appears as a contingent intervention device that, as an alternative to other solutions, such as the individual houses, the cluster housing, and the tall buildings, can integrate and/or replace the traditional city layout. The contribution traces the genealogy and prerogatives of this unusual morphotype, not attributable to any conventional typological classification, assuming its rediscovery and re-proposition also in an empirical key, starting from the indispensable rethinking of the principles of our living with others, in the belief that to survive in the cities that we have irreversibly transformed, we must learn to think in a new way.